Skin stapler versus sutures in abdominal wound closure - Varghese, Fobin; Gamalial, Jose; Kurien, John S. (International Surgery Journal, 2017)
Background: Wound closure is as important as any other action performed by the surgeon. Apart from the need for producing a healthy and strong scar, it is the surgeon’s responsibility to ensure its aesthetically pleasing physical appearance. Skin staples are an alternative to regular sutures in offering this advantage. The present study has helped to highlight the benefits of skin stapler. Methods: Out of the 120 participants, 60 underwent skin closure with Stainless steel skin staples and the remaining 60 with non-absorbable Polyamide mattress sutures randomly. They all received one mandatory dose of pre-operative parenteral antibiotic 1 hour prior to the incision. On the 3rd postoperative day, the wound was evaluated for inflammation, infection and wound gape. Participants were re-evaluated for infection/gape/inflammation during follow-up on 7th day. The wounds were evaluated at 1 months follow up which were rated for cosmesis by Visual Analogue Score. The data was coded and entered in Microsoft excel and then analysed using statistical software SSPS. Results: Study population consisted of 79 males (65.8%) and 41 females (34.2%). Mean age of the study population was 49.35 with an SD 16.739. Wound infection was found to be higher in stapler group (30%) when compared to conventional suture group (11.7%)which was found to be statistically significant with chi-square value 6.114 and p value 0.013. Mean time for closure was significantly shorter in stapler group 4.55 minutes, when compared to suture group (11.22 minutes). Better cosmetic outcome was observed in conventional suture group. Conclusions: Preventing wound infection, especially in abdominal wounds, is of importance as it may lead to wound gaping. Incidence of post-operative wound infection was more with skin staples. Cosmesis is essential and important aspect in this day and age. A cosmetic scar not only gives satisfaction to the patient but also mental ease to the surgeon. Conventional sutures provided better cosmetic result when compared with skin staplers.